Stereotype of Racial issue on #starterpack - Ayedoji, Hakeemi Harris (Universitas Ahmad Dahlan, 2021)
Semiotic comes from Greek word which is semeion (sign). Yet, generally, semiotics is a study which concern about the existence of sign in society. We could find sign everywhere, from the form of words, images, objects, etc. Thus, the object of semiotics could be anything. But, Charles Sanders Pierce explain sign in a different way. According to Pierce’s study, something could be categorized into sign if it could be taken part in the triadic relation. Semiotic study is used in analizing the research. The main data of this research is the #starterpack tweets in Twitter. The data used is focused in the #starterpack tweets with white and black people context from 2019-2020. While the supporting data for this research are from the journals, books, internet sources, and dictionaries. To collect the data, the research used the observation method and use note technique. While, the research used the triadic signs in by Charles Sanders Pierce to analyze the data. From the analizing, the researcher got 40 #starterpack tweets with mostly 4 images in it. Those tweets could be divided to 20 white people #starterpack and 20 black people #starterpack tweets. All the data are analyzed with the triadic signs which are signs, objects, and interpretations. The signs that had been analyzed show objects and interpretations which lead to the gap between white and black people. Those gaps then lead to stereotypes on white and black people. Moreover, the data lead to 6 factors of stereotypes. Those factors are nationatility, personal integrity, curiosity, adaptation, homogeneus neighborhood, and common shared information.